RELIGIOUS-SPIRITUAL CONFLICTS OF CHİLDREN İN ADOLESCENCE WITH THEIR FAMİLY - Rizvance Masan, Sehida; Koca, Mesut (International Scientific Journal Vision, 2023)
In this article, the issue of religious and spiritual conflict, which is one of the factors that lead to conflict in the intra-family communication of adolescent children, is discussed as a result of religious interpretation, practice and expectations of family members from each other. Especially the adolescent period in which conflicts are intense is examined by considering the family conflicts, adolescent characteristics, religious learning stages and conflict types. The severity, duration and permanent effects of conflicts were examined by relating them to family types, and it was emphasized how the different attitudes and attitudes of different family types such as conservative family, authoritarian family, introverted family, consistentinconsistent family, and democratic family affected the conflict. This study is an article written by reviewing the literature about how conflict affects what type of family, how to deal with it and the duty of family members. In the last part, the article is concluded by listing the recommendations for avoiding conflicts or overcoming the conflicts with the least damage.